IDENTIFICATION OF POTENCY AND PROBLEM OF SLUMS AREA IN KAPUAS REGENCY - Amiany (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2017)
Indonesia as a developing country with an unstable demographic condition is reflected in an uncontrolled population growth rate. The severity of the large population is not accompanied by improvement and good economic growth. Impaired economic conditions further increase the poverty rates in Indonesia which impacts on the degradation of physical and non-physical conditions of life and livelihoods of the community which is clearly and clearly reflected in the declining quality of the environment in which people live. Even the worst is the formation of slums or slums. Slum areas in Kapuas Regency are dominant in the riverbanks. In accordance with the slum area criteria that the area has irregular, densely populated, unsuitable quality of buildings, and are not equipped with proper utilities (roads, clean water, waste water, drainage and waste disposal) with community income levels the low one. Handling the Problem of Slum Settlements is part of the anticipation of urban impacts from the improvement of the function of the region into a center of growth and to plan the space of more humane settlements in the future. Less-integrated and less targeted housing and settlements, and less attention to the completeness of basic infrastructure and facilities such as clean water, sanitation, waste management systems and rain drainage channels, will tend to degrade environmental quality or later be terminated as